(untitled) (Bangladesh Journal of Infectious Diseases, 2020)
COVID-19(Corona virus disease 2019), which starts from Wuhan, China on December, 2019 spread rapidly to different countries of the world including Bangladesh. It affects huge impact on health care system. It’s a new disease with multisystem involvement. Physicians are experiencing new presentation of different cases and rare complication including arterial thrombosis. Few data is available regarding arterial thrombosis in SARS-CoV-2 infected patients. We are currently fighting with a 60 year old lady suffering from COVID-19 pneumonia with other co-morbidities developed severe arterial occlusion of right leg despite of taking anti platelet for long time for another cause. Patient developed irreversible right lower limb ischemia not improving with continuous infusion of unfractionated heparin followed by severe pulmonary embolism. So further study and recommendations will need to evaluate the cases and treatment in COVID-19 Patients with rare presentation. Bangladesh Journal of Infectious Diseases, October 2020;7(suppl_2):S50-S56